Chewing gum: Production, quality parameters and opportunities for delivering bioactive compounds - Konar, Nevzat; Palabiyik, Ibrahim; Toker, Omer Said; Sagdic, Osman (ELSEVIER SCIENCE LONDON, 2016)
Background: Chewing gum has an amazing statistics. The entire industry is worth $25 billion and annually 1.74 trillion sticks of chewing gum are produced. It would account for 290 billion hours' duration of staying in mouth if each piece of gum was chewed for 10 min every year. Concerning these statistics at least smoke cessation, oral health and new form of drug delivery system potentials of chewing gum are clear. Therefore, fundamentals of chewing gum should be realized in detail to take the advantage of this product. Scope and approach: In this review, due to limited studies concerning chewing gum in food science and technology area, key points in production, quality parameters and bioactive compounds delivering properties of chewing gum were reviewed with aim to show promising study areas to researchers. Production of different types of gums, ingredients used, sensory and texture properties and potential future functions of chewing gums were discussed with a special emphasis on the bioactive compounds carrier properties of chewing gum. Key findings and conclusions: Encapsulation not only improved a sensation of flavor for a long period when applied in the chewing gum but also had a potential to give functionality to chewing gum. Only recently the idea of healthy chewing gums and using chewing gum as an alternative form of drug delivery system have been developed. Therefore, food technologists should give attention to this promising subject of producing chewing gums having long lasting flavors, being biodegradable and forming a type of functional confection consumed with pleasure by everyone. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Chewing gum; Flavor; Texture; Bioactive compounds; FLAVOR RELEASE; TIME-INTENSITY; SENSORY PROPERTIES; CUSTARD DESSERTS; MODEL; PERCEPTION; WEIGHT; FAT; Food Science & Technology